Teaching sustainability in Higher Education language courses: language teachers’ practices, attitudes and justifications - Maijala, Minna; Saikkonen, Loretta; Malessa, Eva; Laine, Päivi; Mutta, Maarit (Walter de Gruyter GmbH, 2026)
Education for Sustainable Development (ESD) has received increased attention in university-level teaching over the past few decades. This article examines the attitudes of university language centre teachers (N = 43) in Finland towards sustainable development (SD) and the methods they use to implement ESD. The quantitative data were analysed using percentage distributions and correlation analysis, while the open-ended responses were examined using data-driven qualitative content analysis. The teachers’ attitudes towards sustainability in language teaching were generally positive. More than half of them created their own teaching materials, most commonly using pair or group discussions to teach SD topics. The reasons why teachers addressed sustainability topics into their teaching were categorised into teacher-driven, student-driven, language-related and external reasons. Teacher-driven reasons emerged as the most prominent, reflecting motivations rooted in the teachers’ own initiative and values. These reasons centred on encouraging students to change their behaviour, strengthen their critical thinking skills and contribute to positive change. For student-driven reasons, language teachers emphasised students’ interest and motivation to learn about SD topics as well as the importance of ESD for students’ future careers.